Primary care workforce paradox: A physician shortage and a PA and NP surplus. Issue 10 (October 2021) - White, Ryan; Keahey, David; Luck, Morgan; Dehn, Richard W.
ABSTRACT: Objective: Primary care workforce projections continue to predict significant physician shortages. An oversupply of primary care physician assistants (PAs) and NPs also is predicted. This paradox calls into question the assumptions that underlie workforce projection models, which likely underestimate the primary care contributions of PAs and NPs. Methods: Federally qualified health center data from the 2016-2019 Uniform Data System were used to calculate the number of clinic visits per full-time equivalent (FTE) physician, PA, and NP. Visits per FTE were compared across provider type to determine provider-specific productivity ratios. Results: The combined PA and NP productivity ratio increased relative to physicians in each year, ranging from 0.85 in 2016 to 0.88 in 2019. Clinic visits per FTE for PAs and family physicians were nearly equivalent. Conclusions: Primary care workforce projection models should be reexamined to more accurately capture the productivity of PAs and NPs.